Choroidal Neovascularization Associated with Morning Glory Syndrome: A Case Report - Sato, Shigeru; Morimoto, Takeshi; Tanaka, Sayaka; Tsujikawa, Motokazu; Nishida, Kohji (Archives of Clinical and Medical Case Reports, 2020)
Morning glory syndrome (MGS) is a congenital optic disc anomaly caused by abnormal closure of the embryonic fissure. Retinal detachment is commonly associated with MGS, though the association of choroidal neovascularization (CNV) with MGS is rare. Herein, we report a case of CNV associated with MGS, which was successfully treated with a single intravitreal injection of bevacizumab. A 32-year-old Japanese woman consulted at our clinic for blurred vision in her left eye for five days. Her best-corrected decimal visual acuity (BCVA) was 1.5 (S-1.0) OS. The fundus examination revealed subretinal hemorrhage associated with MGS in the temporal margin of the optic disc. As she was pregnant, we planned to continue follow-up without further invasive testing and treatment; however, her visit to the hospital was interrupted. Ten months later, she returned with complaints of poor vision and central scotoma in her left eye for six months. The BCVA was 0.5 (S-1.0/C-1.0/45°) OS. The fundus examination showed that subretinal hemorrhage increased, and the subretinal fluid extended below the fovea. Multimodal imaging revealed type 2 CNV on the temporal and nasal disc margins. After she received an intravitreal injection of bevacizumab (1.25 mg), rapid absorption of subretinal fluid and regression of CNV were observed. The BCVA improved to 1.5 (S-0.5/C-0.75/35°) OS. No recurrence of CNV was observed for 26 months after the injection. During the follow-up of MGS cases, we should pay attention, not only to retinal detachment, but also to the occurrence of CNV around the disc margins.